Factors of local conversion of iodothyronines correlate with indicators of hormonal, biochemical, and hematological profiles in patients with spinal canal and dural sac stenosis of the lumbar spine - L. V. Rodionova; A. P. Zhivotenko; L. G. Samoilova; D. A. Barkhatov; A. S. Pushkarev; S. N. Larionov; V. E. Potapov; V. A. Sorokovikov (Acta Biomedica Scientifica, 2022)
In order to find out the mechanisms of pathogenesis of degenerative-dystrophic diseases of the spine, it is of particular interest to search for body parameters which are directly or indirectly interrelated with the key factors of peripheral conversion of nidus iodothyronines and constitute a system of network interactions, affecting metabolic indicators at the local and systemic level.The aim. To search for correlations of local key factors of peripheral conversion of Ligamentum flavum iodothyronines with indicators of biochemical, hematological and hormonal blood profiles of patients with stenosing processes of the spinal canal and dural sac in the lumbar spine.Materials and methods. 33 patients (15 males, 18 females) with stenosing processes of the spinal canal and dural sac in the lumbar spine were examined (mean age – 45.73 ± 1.95 years). The expression of deiodinase genes and other candidate genes was determined in Ligamentum flavum biopsies collected during surgical treatment. Biochemical, hematological and hormonal parameters were determined in peripheral blood. The resulting data array was processed in order to find correlations between the parameters of systemic and local metabolism.Results. The relationships of deiodinases with the expression of GDF5, MMP1, MMP3 and TIMP1 in Ligamentum flavum (p < 0.05) were found. Of the hormonal profile of the blood serum, the most significant indicators were thyreotropin, free triiodothyronine and thyroperoxidase antibodies. In the biochemical profile, levels of direct bilirubin, total cholesterol, HDL and LDL cholesterol and triglycerides changed along with the expression of deiodinases. Correlative relationships with the expression of deiodinases were found for the following hematological analytes of whole peripheral blood: hemoglobin, mean corpuscular hemoglobin concentration, numbers of granulocytes, lymphocytes, eosinophils, monocytes, band neutrophils, red cell distribution width and platelet crit. The data obtained indicate the involvement of peripheral conversion factors in the pathogenetic process and provide information to form a new view on the pathogenesis of degenerative-dystrophic processes in the Ligamentum flavum of patients with stenosing processes of the spinal canal and the dural sac in the lumbar spine.